Haplotype distribution and genotypic diversity among Angolan children with sickle cell disease - Delgadinho, Mariana (2021)
Sickle cell disease (SCD) is an inherited blood disorder that affects over 300,000 newborns worldwide every year. Despite being a monogenic disease, SCD shows a remarkably high clinical heterogeneity, and analysis of the HBB gene cluster has revealed five distinct haplotypes: Senegal (SEN), Benin (BEN), Central African Republic (CAR), Cameroon (CAM), and Arab-Indian (ARAB). The aim of this study was to assess the frequency of HBB haplotypes, as well as to correlate other genetic predictors that could have an impact on SCD phenotype in an Angolan pediatric population.